Organizational Alignment in the Digital Era: A Qualitative Exploration of Marketing-Sales-IT in Industrial Companies - Chalirafi; Cahyo, Rico Dwi; Akhyar, Chairil; Syamni, Ghazali (APMBA (Asia Pacific Management and Business Application), 2026)
Digital transformation has accelerated the integration of marketing, sales, and information technology (IT) functions in managing customer interactions. However, the mechanisms through which these functions interact and achieve strategic alignment remain insufficiently understood. Concurrently, the emergence of customer success management (CSM) requires sales professionals to extend their responsibilities beyond the transaction phase to encompass ongoing customer experience and success. This study aims to explore the forms and dynamics of organizational alignment among marketing, sales, and IT actors using a qualitative case study approach. Data were collected through in-depth interviews with four M–S–I triadic groups, including executive leaders, representing all stages of the customer journey. The analysis focuses on identifying interaction patterns, coordination challenges, and key factors influencing the effectiveness of cross-functional alignment. The findings reveal six primary dimensions comprising twenty attributes that collectively define the construct of organizational alignment. These insights are synthesized into a conceptual framework termed COMPLY, designed as an operational tool to assess and refine cross-functional M–S–I alignment. Furthermore, the study proposes several propositions that explain intra-dimensional relationships and intervention mechanisms across dimensions to enhance collaborative effectiveness. This research contributes to the literature on organizational alignment and customer success management, while also offering a practical framework for managers to optimize marketing–sales–IT integration in support of sustainable CSM implementation.